Amorphous silica reduces N2O emissions from arable land at the field plot scale - Hoffmann, Mathias; Diaz, Oscar Rodrigo Monzon; Zentgraf, Isabel; Al-Hamwi, Wael; Dubbert, Maren; Stein, Mathias; Holz, Maire; Schaller, Jörg (Frontiers in Environmental Science, 2025)
IntroductionIncreasing greenhouse gas emissions pose a strong threat due to accelerating global warming. N2O emissions are highly important in this regard as N2O is a very powerful greenhouse gas. Agriculture is the main human-induced source for N2O emissions, contributing roughly 60% to total N2O emissions. Soil amorphous silica (ASi) contents are reduced in arable soils due to yearly exports by crop harvest as most crops are silicon accumulator plants. Most recently it has been shown that ASi is increasing water and nutrient availability in soils. Both factors are known to directly and indirectly affect N2O emissions from agroecosystems.MethodsIn this study we conducted a field plot trial on arable soil depleted in ASi and fertilized this soil to its pre-agricultural ASi level.ResultsOur data clearly shows that increasing soil ASi to a pre-agricultural level decreased seasonal N2O emissions by ∼30%.DiscussionThis reduction of N2O emissions due to ASi might be of global relevance as agricultural practice has reduced the ASi content in agricultural soils. If future studies confirm the effect of ASi on N2O emissions, the soil ASi depletion by agricultural practice in the last decades may have led to a substantial increase of N2O emissions.